Effectiveness and safety of treating carotid atherosclerotic plaques with the method of nourishing qi, promoting blood circulation and expelling phlegm: A systematic review and meta-analysis - Li, Jia; Du, Yuying; Cai, Chao; Liu, Fuming (Frontiers in Pharmacology, 2022)
Objectives This meta-analysis aimed at evaluating the effectiveness and safety of Chinese medicine(TCM), which nourished qi, promoted blood circulation, and expelled phlegm(YQHXZT), in treating carotid atherosclerosis (CAS) from an immunological perspective. Background The incidence of CAS has been increasing and tends to be younger. Although western medicine is effective, there are some limitations. TCM has certain advantages over the multichannel and multitarget treatment strategies in slowing down the process of CAS. However, there is no comprehensive review in this field. Methods Nine databases were searched from January, 2012, to September, 2022. After applying the inclusion and exclusion criteria to the RCTs, research quality evaluation and data extraction were conducted, and a meta-analysis of the articles was performed. The GRADE was used to assess the quality of the evidence. Results Fourteen RCTs involving 1191 patients were identified. The results indicated that the experimental group was more effective in improving carotid intima-media thickness(CIMT)[SMD=-0.97, 95%CI(-1.30,-0.65), P＜0.00001], reducing carotid plaque area [SMD=-1.98, 95%CI(-3.06,-0.89 ), P=0.0003], lowering hs-CRP [SMD=-1.33, 95%CI(-1.59,-1.06), P＜0.00001] and LDL-C levels [SMD=-0.60, 95%CI(-0.83,-0.38), P＜0.00001]. Moreover, the experimental group was superior to peak systolic blood flow velocity(PSV) [SMD=-0.37, 95%CI(-0.59,-0.16), P =0.0007] , clinical efficacy [RR = 1.64, 95% CI (1.39, 1.94), P<0.00001] and plaque area efficacy [RR = 1.36, 95% CI (1.22, 1.52), P<0.0001]. The adverse reactions were not statistically significant in the two groups [RD=-0.01, 95% CI (-0.04,0.01), p=0.17]. The results of grade evaluation suggested that the outcome indicators LDL-C, hs-CRP, plaque area efficacy, PSV, and adverse events were moderate. CIMT, plaque reduction area, and TCM clinical efficacy were low-quality. Conclusion The combination of YQHXZT can alleviate the process of CAS by inhibiting the thickening of CIMT, reducing plaque area and lowering hs-CRP and LDL-C levels. The mechanism may possibly be related to reducing lipid deposition and inhibiting the inflammatory response. Besides, the combination did not increase the risk of adverse effects. However, more well-designed RCTs are needed in the future.